Osteoporosis among the Chronic Obstructive Pulmonary Disease Patients - Rashid, Md Haroon ur; Chowdhury, Rezaul Karim; Amin, Mashah Binte; Khan, Md Momenuzzaman (Anwer Khan Modern Medical College Journal, 2020)
Background: COPD is a widely prevalent disease with high morbidity and mortality and is associated with various comorbidities, among which is osteoporosis. However, osteoporosis is often undiagnosed in these patients. Material and methods: This study was conducted on 40 patients with COPD and 15 healthy controls (the control group). They were selected from EMCH from Jan 2015 to Dec 2017. All participants were subjected to detailed clinical history taking, a thorough clinical examination, plain chest radiography (posteroanterior and lateral views), blood sampling for complete blood picture, erythrocyte sedimentation rate, and serum calcium and phosphates, ventilatory function tests (spirometry), and measurement of bone density using dual-energy X-ray absorptiometry (DEXA). Results: The results of this study revealed prevalence of osteoporosis was higher in the COPD group compared with the control group (P < 0.00). Prevalence of osteoporosis increased with increasing severity of COPD (P < 0.00). Conclusion: Osteopenia and osteoporosis are more prevalent in COPD patients than in healthy controls and the severity of osteoporosis increases with increasing severity of COPD. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 16-21